ANALISIS TENTANG METODE PENDIDIKAN AKHLAK DALAM QS. YUSUF SERTA IMPLEMENTASINYA PADA SMK AL-INSAN CILEGON - Musyafa’ah Musyafa’ah (QATHRUNÂ, 2020)
Al-Qur'an is an inspiration in building moral morals, as a condition for concepts and moral values ​​that are very relevant to be used as a reference in fostering community morals. The formulation of the problem in this study is as follows: 1. How is the application of moral education values ​​in the QS. Yusuf at Al-Insan Cilegon Vocational School? 2. What are the Inhibiting and Supporting Factors for the Implementation of Moral Education in Al-Insan Vocational School? The Research Objectives are: 1. To find out the application of moral education values ​​in the QS. Yusuf at Al-Insan Vocational School Cilegon 2. To find out inhibiting factors and Supporting the Implementation of Moral Education at Al-Insan Vocational School. This research uses Library Research, which is research by collecting data that is related to the object of research, both primary data (Al-Qur'an, Surah Yusuf), Secondary (books, articles, journals). While the data collection method is by documentation, interview. The results showed that the value of moral education in Q.S. Yusuf is patient, piety, sincerity, justice, honesty, trustworthiness and gratitude, the inhibiting factor is due to different family backgrounds, so it is possible that not all students learn religion at home and the supporting factors are patience, enthusiasm and persistence from educators who become the main key to direct and provide examples to students.